Electrospinning : From Basic Research to Commercialization - Kny, Erich; Ghosal,Kajal; Thomas, Sabu (Croydon : Royal Society of Chemistry, 2018)
Electrospinning is a technique used to produce nanofibres from a polymer solution using an electrostatic force. The technology is now being used to create materials for a wide variety of uses from tissue engineering and 3D printing to packaging materials and electronic sensors. This new book focusses on the recent developments in their design, process parameters and polymers-selection to enable the commercial applications of electrospinning. The initial chapters introduce the technique and then specific chapters focus on the different application areas showing the various approaches for successful implementation of this fabrication process towards commercialization from basic research and development. The book will be suitable for graduate students, academics and industrial entrepreneurs in materials science, polymer science and chemical engineering as well as those interested in the energy and health applications of the materials.
Keywords: Electrospinning